Hombre [videorecording (DVD)] - Ritt, Martin, 1914-1990; Newman, Paul, 1925-2008; March, Fredric, 1897-1975; Boone, Richard; Cilento, Diane; Mitchell, Cameron, 1918-1994; Leonard, Elmore, 1925-2013 (Twentieth Century Fox Home Entertainment, 2002)
A white man raised as an Apache faces confrontation with society.